The Impact of Polygamous Parents on Children's Stress Level Development - Marzuqi, Muhammad Syafiq; Dinniar, Cindy Gefa Maulid (International Journal of Social and Management Studies, 2023)
Polygamy means multiple marriages. The etymological definition can be explained and understood that polygamy is a marriage in which one party (husband) marries more than one wife at the same time. This means that the wives are still dependent on the husband and are not divorced and are still valid as his wives. Many adults do not realize the mental importance of a child living as a "broken home child". The mentality that should be created or built from the family environment is destroyed by a family situation that is no longer intact or already feels strange with the presence of other people. By getting closer to the child, we will understand how they live a very complicated life. As parents or adults we can also understand that it is not only the mother who is hurt. The child of the polygamist's first wife also feels the same or even more. Prioritizing the happiness of parents is not wrong. But we also need to consider the happiness of the child (first wife). There are many ways we can find out about our child's mental health problems. One of them also comes from the mother's (first wife) approach to the child. We can also consult an expert. The child (from the first wife) bears more of the burden of trauma, especially for girls who will be afraid of being close or having a relationship with the opposite sex. Then, boys will experience a lot of crises of distrust of adults. They have many worries. Be it now or in the future. There will also be other problems such as sexual abnormalities in the child (from the first wife).